Small range size and narrow niche breadth predict range contractions in South African frogs. Issue 5 (20th December 2012) - Botts, Emily A.; Erasmus, Barend F. N.; Alexander, Graham J.; Lawlor, Joshua
Abstract Aim Small range size often increases a species' susceptibility to decline. A narrow ecological niche is one factor that may cause species to inhabit a small range. We investigated whether specialized niches have made South African amphibians more vulnerable to range contractions. Location South Africa. Methods The South African Frog Atlas Project is a comprehensive dataset that combines a recent biological survey with historical species distribution data. It provided an opportunity to quantitatively compare range sizes, niche breadth and range size changes for amphibian species. An ecological niche factor analysis supplied comparative measures of climate and habitat niche breadth for each species. Niche breadth was related to range size changes using linear regressions. Ranges of species with narrow habitat niches were spatially compared to areas of high land transformation. Results Small range size was a significant predictor of range contractions for South African amphibians (R2 = 0.35). Furthermore, species with narrow habitat (R2 = 0.25) and climate (R2 = 0.21) niches had experienced more severe range contractions than species with broader niches. Among only endemic species, climate specialization (R2 = 0.27) became a better predictor of range size change than habitat specialization (R2 = 0.21). Habitat specialists were concentrated within two areas of endemism that also had higher than average (P < 0.0001) levels of land transformation. Main conclusions Small range size increased species' likelihood of experiencing range contractions. Narrow niche breadth was also a significant predictor of range contractions, indicating that specialization may contribute to higher decline risk in small‐range species. The role of climate specialization in predicting range contractions among endemics emphasizes the potential impacts of climate change. The spatial synchrony of contracting habitat specialists in highly transformed areas of endemism suggests that conservation efforts should target specialist species and the ecosystems where many such species occur.